Al-Raqabatul al-musharafu 'ala al-masharif al Islamiyah: minhaju fikriy,wa dirasah mai... - NASHIR, Al-Gharib (Al-Ma'had Al-Alamy, Kairo, 1996)
Al-Raqabatul al-musharafu 'ala al-masharif al Islamiyah: minhaju fikriy,wa dirasah ...